The prevalence of chronic diabetic complications and metabolic syndrome is not associated with maternal type 2 diabetes - Scheffel,R.S. (2008)
The maternal history of type 2 diabetes mellitus (DM) has been reported more frequently in patients with type 2 DM than paternal history. The aim of the present study was to determine if there was an association between maternal history of DM and the presence of chronic complications or metabolic syndrome (MetS) in patients with type 2 DM. A cross-sectional study was conducted with 1455 patients with type 2 DM. All outpatients with type 2 diabetes attending the endocrine clinics who fulfilled the eligibility criteria were included. Familial history of DM was determined with a questionnaire. Diabetic complications were assessed using standard procedures. The definition of MetS used was that of the World Health Organization and the National Cholesterol Education Program's Adult Treatment Panel III report criteria. Maternal history of DM was present in 469 (32.3%), absent in 713 (49.1%) and unknown in 273 patients (18.7%). Paternal history of DM was positive in 255 (17.6%), negative in 927 (63.8%) and unknown in 235 patients (16.1%). The frequency of microvascular chronic complications in patients with and without a positive maternal history of DM was similar: diabetic nephropathy (51.5 vs 52.5%), diabetic retinopathy (46.0 vs 41.7%), and diabetic sensory neuropathy (31.0 vs 37.1%). The prevalence of macrovascular chronic complications and MetS was also similar. Patients with type 2 DM were more likely to have a maternal than a paternal history of DM, although maternal history of DM was not associated with an increased prevalence of chronic complications or MetS.